Educational and Career Trajectories of the Russian Youth in a Longitudinal Perspective: A Case of University Graduates - Maltseva, Vera; Rozenfeld, Natalia (Voprosy obrazovaniya / Educational Studies Moscow, 2022)
Education and labor market outcomes of the Russian graduates are vastly studied, including their employment status, salaries, types of universities and majors they study. However, there is a lack of research of the graduates’ typical paths in education and labor market, whether they fit the conventional trajectory high school–university–permanent employment. Another question is how social background and human capital differentiate trajectories and predict a path, which graduate opts to. In this article, we address both questions. Employing the longitudinal panel study “Trajectories in Education and Careers” we examine the nine-year trajectories of those who earned a university diploma by the age of 25. In our research, we use sequence analysis to identify trajectories and regression analysis to estimate the probability to follow each trajectory depending on individual characteristics–socio-economic status and human capital–while controlling for demographic variables. We identify nine typical trajectories, including several types of a linear path, various career-oriented trajectories, a reverse and a delayed path, unstable and nontraditional trajectories. This set of education-career paths largely corresponds to foreign studies, but the Russian graduates’ trajectories turn out to be smoother. At the same time, individual factors of human capital and socio-economic status moderate education-career paths. The probability of following trajectories with prolonged education (with a post-bachelor’s degree) is significantly higher for high achieving students. Entering early career trajectories is associated with a non–cognitive skill–openness to experience. Socio-economic status differentiates two early career trajectories: "accelerated adulthood" for those with low SES and "encouraged professionalization", which is associated with high SES. Following an unstable trajectory is not associated with either socio-economic status or academic performance (cognitive skills) but is associated with low awareness about the field of study when entering a university (ill-informed choice).